MATHIAS, Suzeley Kalil (Org.). Sob o signo de Atena: gênero na diplomacia e nas Forças Armadas. - Moreira, Rosimeri (Revista Estudos Feministas, 2011)
MATHIAS, Suzeley Kalil (Org.). Sob o signo de Atena: gênero na diplomacia e nas Forças Armadas.